F19. TELOMERE SHORTENING IN YOUNG PEOPLE WITH FIRST EPISODE PSYCHOSIS: A 12-MONTH FOLLOW-UP STUDY. (1st April 2018) - Fraguas, David; Recio, Sandra; Diaz-Caneja, Covadonga M; Blasco, Maria A; Moisés, Ana Carolina; Arango, Celso
Abstract: Background: Short telomere length is a biomarker of cell oxidation and aging. Patients with first-episode psychosis (FEP) have been reported to have shorter telomeres than healthy controls (HC), suggesting that there is a premature and accelerated cellular aging in FEP. However, there are not data on longitudinal changes of telomere length in people with FEP relative to HC. We present preliminary results on 1-year longitudinal changes in peripheral blood mononuclear cells (PBMCs) telomere length and the proportion of PBMCs with short telomeres in young people with FEP and HC. Methods: 16 young patients with FEP (43.8% female, mean age 17.9 years) and 21 young HC (61.9% female, mean age 16.6 years) were enrolled in the study. PBMCs telomere length and the proportion of PBMCs with short telomeres (i.e. <3kb) were determined using high-throughput quantitative fluorescence in situ hybridization (HT Q-FISH) at baseline (16 patients with FEP and 21 HC) and 12-month follow-up (4 patients with FEP and 4 HC). Results: At baseline, we did not find significant differences in telomere length nor in proportion of PBMCs with short telomeres between FEP patients and HC. During the one-year follow-up, we found a significantly greater loss of telomere length (p=0.019; explained variance=69.7%) and a non-significantly trend for greater increase in the proportion of PBMCs with short telomeres (p=0.097; explained variance=45.5%) in patients with FEP than in HC. Discussion: Telomere length changes during the first years of the illness can represent an early marker of accelerated cellular aging in patients with first-episode psychosis.